Peningkatan Kapasitas Tim Pendamping Keluarga (TPK) dalam Upaya Percepatan Penurunan Stunting di Kabupaten Sragen, Jawa Tengah - Afiatna, Puji; Sugeng Maryanto; Indri Mulyasari; Risma Aliviani Putri; Anisa Puspitasari (UNIVERSITAS NGUDI WALUYO, 2024)
Stunting is a condition of growth failure in children under five resulting from chronic malnutrition, particularly during the first 1,000 days of life. In the body of a stunted child, there are impediments to physical growth and mental development. This is the body's adaptation to malnutrition. The underlying causes of stunting must be addressed so that the impact of stunting is not experienced until adulthood. In 2022, Sragen Regency, Central Java, was identified as a key location for stunting intervention. One of the strategies to accelerate stunting reduction is the provision of assistance to families at risk of stunting. This is carried out by the family support team (TPK) Cadre. The Sragen Regency TPK cadres have provided communication, information, and education to the target group. However, the implementation of this strategy has not been optimised. The cadres lack the requisite skills to prepare materials, create media, and provide education to the target group. They are constrained in their ability to educate target groups about alternative nutrient-dense foods, particularly those derived from local sources in the supplementary feeding program for target groups. Training activities utilize a combination of lecture, discussion, and hands-on preparation of materials and creation of communication, information, and education media according to the target group, video screenings, and demonstrations of nutrient-dense supplementary foods. The activity was attended by 71 representatives of TPK cadres from 10 villages focused on handling stunting in Sragen Regency. The results obtained were increased knowledge and skills of cadres in providing communication, information and education and the provision of nutrient-dense supplementary food. It is recommended that cadres disseminate information about the preparation of materials, the creation of communication, information and education media and alternative nutrient-dense supplementary foods to other cadres in the village. ABSTRAK Stunting adalah kondisi gagal tumbuh pada anak balita sebagai akibat kekurangan gizi kronis terutama pada 1000 Hari Pertama Kehidupan. Di dalam tubuh anak yang stunting terjadi hambatan pertumbuhan fisik dan perkembangan mental. Hal ini sebagai penyesuaian tubuh terhadap kondisi kekurangan gizi. Akar penyebab stunting harus diatasi agar dampak stunting tidak dialami hingga dewasa. Kabupaten Sragen, Jawa Tengah pada tahun 2022 menjadi salah satu lokasi fokus intervensi stunting. Salah satu program percepatan penurunan stunting adalah pendampingan keluarga berisiko stunting yang dilaksanakan oleh Kader Tim Pendamping Keluarga (TPK). Kader TPK Kabupaten Sragen telah memberikan Komunikasi, Informasi dan Edukasi (KIE) pada kelompok sasaran, namun belum dilaksanakan dengan optimal. Kader TPK belum terampil dalam menyusun materi, membuat media dan memberikan edukasi kepada kelompok sasaran. Kader TPK memiliki keterbatasan dalam memberikan edukasi kepada kelompok sasaran mengenai alternatif makanan padat gizi terutama yang berbahan dasar pangan lokal dalam program Pemberian Makan Tambahan (PMT) kelompok sasaran. Kegiatan pelatihan dengan metode ceramah, diskusi dan praktik penyusunan materi dan pembuatan media KIE sesuai kelompok sasaran, pemutaran video dan demonstrasi untuk PMT pada gizi. Kegiatan tersebut diikuti oleh perwakilan Kader TPK dari 10 Desa fokus penanganan stunting di Kabupaten Sragen sebanyak 71 orang. Hasil yang didapatkan adalah meningkatnya pengetahuan, dan keterampilan kader TPK dalam memberikan KIE dan PMT padat gizi. Saran bagi kader TPK adalah meneruskan informasi mengenai penyusunan materi dan pembuatan media untuk KIE dan alternatif PMT padat gizi kepada kader TPK yang anggota kader TPK lain di desanya.